Phenotyping non‐alcoholic fatty liver disease by the gut microbiota: Ready for prime time?. Issue 11 (30th April 2020) - Demir, Münevver; Lang, Sonja; Martin, Anna; Farowski, Fedja; Wisplinghoff, Hilmar; Vehreschild, Maria J.G.T.; Krawczyk, Marcin; Nowag, Angela; Scholz, Claus Jürgen; Kretzschmar, Anne; Roderburg, Christoph; Lammert, Frank; et al.
Abstract: Background and Aim: Several studies observed alterations in the gut microbiota in patients with non‐alcoholic fatty liver disease (NAFLD). However, analyzed patient populations and methods strongly differ among these studies. The aim of this study was to prove the reproducibility of published results and to provide a detailed overview of all findings in our NAFLD cohort using next generation sequencing methods. Methods: The individual taxonomic microbiota composition of fecal samples from 90 NAFLD patients and 21 healthy controls was analyzed using 16S rRNA gene sequencing. Study participants were grouped according to their disease stage and compared regarding their gut microbiota composition. Studies were identified from PubMed listed publications, and the results were compared with the findings in our cohort. Results: Results from 13 identified studies were compared with our data. A decreased abundance of the Bacteroidetes and Ruminococcaceae as well as an increased abundance of Lactobacillaceae and Veillonellaceae and Dorea were the most frequently reported changes among NAFLD patients in 4/13, 5/13, 4/13, 2/13, and 3/13 studies, respectively. Even though these alterations in the gut microbiota composition were also observed in our patient cohort, the majority of published differences could not be reproduced, neither in our own nor in other NAFLD cohort studies. Conclusion: Despite repeatedly reproduced abundance patterns of specific bacteria, the heterogeneous study results did not reveal a consistent disease specific gut microbiota signature. Further prospective studies with homogenous patient cohorts and standardized methods are necessary to phenotype NAFLD by the gut microbiota.